Early Inflammatory Signatures Predict Subsequent Cognition in Long-Term Virally Suppressed Women With HIV - Rubin, Leah H.; Xu, Yanxun; Norris, Philip J.; Wang, Xuzhi; Dastgheyb, Raha; Fitzgerald, Kathryn C.; Keating, Sheila M.; Kaplan, Robert C.; Maki, Pauline M.; Anastos, Kathryn; Springer, Gayle; Benning, Lorie; et al. (Frontiers in Integrative Neuroscience, 2020)
Immunologic function is an important determinant of cognition. Here we examined the contribution of early immune signatures to cognitive performance among HIV-infected, virally suppressed women (HIV+VS) and in HIV-uninfected (HIV-) women, we measured serum inflammatory markers, developed combinatory immune signatures, and evaluated their associations with cognition. Forty-nine HIV+VS women in the Women’s Interagency HIV Study (WIHS) who achieved viral suppression shortly after effective antiretroviral therapy (ART) initiation, and 56 matched HIV- women were selected. Forty-two serum inflammatory markers were measured within two years of effective ART initiation for HIV+VS women, and at an initial timepoint for HIV- women. The same inflammatory markers were also measured approximately 1, 7, and 12 years later for all women. Of the 105 women with complete immune data, 83 (34 HIV+VS, 49 HIV-) also had cognitive data available 12 years later at ≥1 time points (median=3.1). We searched for combinatory immune signatures by adapting a dynamic matrix factorization analytic method that builds upon Tucker decomposition followed by Ingenuity® Pathway Analysis to facilitate data interpretation. Seven combinatory immune signatures emerged based on the Frobenius residual. Three signatures were common between HIV+VS and HIV- women, while four signatures were unique. These inflammatory signatures predicted subsequent cognitive performance in both groups using mixed-effects modeling, but more domain-specific associations were significant in HIV+VS than HIV- women. Leukocyte influx into brain was a major contributor to cognitive function in HIV+VS women, while T cell exhaustion, inflammatory response indicative of depressive/psychiatric disorders, microglial activity, and cytokine signaling predicted both global and domain-specific performance for HIV- women. Our findings suggest that immune signatures may be useful diagnostic, prognostic, and immunotherapeutic targets predictive of subsequent cognitive performance. Importantly, they also provide insight into common and distinct inflammatory mechanisms underlying cognition in HIV- and HIV+VS women.